Advanced Structural Analysis Of Silicon Solar Cells - Papež, Nikola (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2019)
The study investigates the structural imperfections of photovoltaic cells based on polycrystalline silicon. Experimental characterization focuses in particular on the degradation and defects analysis. Two modern techniques were used – scanning electron microscopy (SEM) with electron beam induced current (EBIC) and 3D digital optical microscopy. The properties and range of cell defects that can significantly affect its function were characterized with this inspection and failure Analysis.
Keywords: SEM; EBIC; optical microscopy; solar cells; defects